A clinical case study of seven patients of autonomic dysfunction in post COVID-19 conditions with fever as the main clinical symptom: a case series - Haihong, Liu; Nannan, Xu; Xiangzhu, Meng; Gang, Wang (Annals of medicine (Helsinki), 2024)
Many publications have reported that acute COVID-19 infection can cause autonomic dysfunction. In this series, we described seven patients who had recurrent fever after acute COVID-19 infection, and the possible pathophysiological basis is autonomic dysfunction. This was a retrospective study conducted at the Qilu Hospital of Shandong University from January 2023 to March 2023. Patients who were hospitalized in the Department of Infectious Diseases with a diagnosis of fever of unknown origin. Between January and March 2023, a total of seven patients with autonomic dysfunction in post-COVID condition, who had recurrent fever accompanied by electrolyte imbalances and other manifestations of autonomic dysfunction. The median age of these patients was relatively high, and they were mostly indoor workers with comorbidities such as diabetes and chronic hypertension. Physical cooling and correction of electrolyte imbalances with medication were effective treatments. The COVID-19 infection can lead to autonomic dysfunction, which manifests not only as tachycardia and blood pressure abnormalities, but may also be the pathophysiological mechanism underlying recurrent fever in post-COVID cases.